The Carotid Conundrum: Evaluating Stenting Versus Endarterectomy in Modern Practice - Toprak, Burak; Kanat Toprak, Çise (Scientific Reports in Medicine, 2025)
Objective:This review aims to assess the clinical outcomes, safety, and efficacy of carotid artery stenting (CAS) compared to carotid endarterectomy (CEA) for managing carotid artery stenosis, emphasizing risk stratification based on patient age and symptomatic status. Proper risk stratification is vital to achieve personalized treatment and improve outcomes.Methods:We analyzed data from randomized controlled trials (RCTs) and meta-analyses comparing CAS and CEA in symptomatic and asymptomatic patients. Notably, recent studies like Müller et al. (2021) offered detailed insights into how outcomes vary across patient subgroups. Primary endpoints include perioperative stroke, myocardial infarction (MI), and restenosis, while secondary outcomes such as quality of life and recovery times were considered.Results:CAS was linked to a higher risk of periprocedural stroke, particularly in older patients, while CEA showed a higher incidence of perioperative MI. Long-term follow-up revealed that CAS had a higher rate of restenosis, particularly in patients with calcified plaques. CEA was shown to reduce perioperative stroke risk significantly, especially in patients over 70 years old, highlighting age as a critical factor in determining long-term success. Thorough preoperative imaging is essential when selecting candidates for CAS, particularly in cases with significant calcification.Conclusion:CAS is suitable for younger, low-risk patients, but CEA remains the optimal choice for older individuals due to its lower stroke risk. Treatment should be individualized, accounting for factors like age, comorbidities, and anatomical considerations.